Abciximab therapy is associated with increased platelet activation and decreased heparin dosage in patients with acute myocardial infarction - Piorkowski, Michael; Priess, Jana; Weikert, Ulf; Jaster, Markus; Schwimmbeck, Peter-Lothar; Schultheiss, Heinz-Peter; Rauch, Ursula (Thrombosis and Haemostasis, 2005)
The inhibition of the glycoprotein (GP) IIb/IIIa receptor for reducing periprocedural ischemic events in patients undergoing coronary intervention is known to influence platelet reactivity. Suboptimal doses of GP IIb/IIIa antagonists have been suggested to be prothrombotic and proinflammatory. This study was performed to observe platelet activation markers, whole blood aggregation and the dosage of unfractionated heparin (UFH) in the presence or absence of the GP IIb/IIIa inhibitor abciximab. Patients with acute myocardial infarction undergoing percutaneous coronary intervention were treated with (n=15) or without (n=15) abciximab. Platelet activation markers were flow cytometrically measured before and after PCI. Whole blood platelet aggregation was tested by a platelet function assay. The patients with abciximab showed a significant increase in platelet activation markers (P-selectin: 7.12 ± 0.36 AU vs 11.05 ± 0.79 AU) and a lower requirement of UFH to prolong aPTT > 60 sec during the infusion. 12 hours after infusion P-selectin level decreased (7.20 ± 0.58 AU), whereas whole blood aggregation was increasing again. After stopping abciximab, requirement of UFH to prolong aPTT increased in the treated group to a greater extent to a level similar to the untreated group even when most of the platelets were still inhibited. The increased platelet activation found at the end of abciximab treatment points to a procoaguable condition that should be carefully monitored and treated by adapting anticoagulation and antiplatelet drugs.
Keywords: Abciximab; heparin; platelet activation